The Influence of Work Environment and Work Culture on Employee Achievement at the Secretariat of The Human Resources Development Agency, Ministry of Home Affairs - Budi Supriyatno; Azis Hakim (The Institute of Academic Research and Publication (IARP), 2023)
The research objective is how much influence the work environment and work culture together have on the work performance of employees at the Secretariat of the Human Resources Development Agency, Ministry of Home Affairs. The purpose of this study is to determine and examine the magnitude of the influence of the work environment and work culture jointly on employee performance at the Secretariat of the Human Resources Development Agency, Ministry of Home Affairs. The research method uses a survey with a quantitative approach that is correlational with the sampling technique used based on the sampling table developed by Isaac and Michael. In this study, the number of samples was 58 respondents. The variables studied were work environment (X1) and work culture (X2) as independent variables, while employee performance was the dependent variable (Y). Based on the results of the research that has been done, namely: 1) Based on the results of hypothesis testing the effect of work environment variables on employee performance at the Secretariat of the Human Resources Development Agency of the Ministry of Home Affairs, it has a strong and significant positive influence, this is indicated by the correlation coefficient value of 0.695 and the coefficient of determination of r2 = 0.483 or 48.3%, this means that 48.3% employee performance is determined by the work environment, the remaining 51.7% is determined by other factors. Furthermore, for the significance test, the t-count value is 7.233 and the t-table value is 2.000. This means that the alternative hypothesis is accepted because t-count (7.233) > t-table (2.000). 2) Based on the results of hypothesis testing the effect of work culture variables on employee performance at the Secretariat of the Human Resources Development Agency of the Ministry of Home Affairs, it has a strong and significant positive influence, this is indicated by the correlation coefficient value of 0.697 and the coefficient of determination of r2 = 0.486 or 48.6%, this means that 48.6% employee performance is determined by work culture, the remaining 51.4% is determined by other factors. Furthermore, for the significance test, the t-count value is 7.276 and the t-table value is 2.000. This means that the alternative hypothesis is accepted because t-count (7.276) > t-table (2.000). 3) To test the double correlation hypothesis of work environment and work culture variables together on employee performance at the Secretariat of the Human Resources Development Agency of the Ministry of Home Affairs, it turns out to have a strong and significant positive influence with a correlation coefficient of 0.739 and a coefficient of determination of r2 = 0.546, this means that together employee performance of 54.6% is determined by the work environment and work culture, the remaining 45.4% is determined by other factors. Furthermore, for the significance test, the F-count value was 33.133 and the F-table value was 3.17. This means that the alternative hypothesis is accepted because of F-count (33.133) > F-table (3.17).